Application of the Orthogonal Test in Basic Control Software Testing for LKJ Device - JIANG Jian; SHANGGUAN Xianan; HE Xiezhen (Kongzhi Yu Xinxi Jishu)
In LKJ basic control software testing, there are many combined test scenes with multiple-input-parameter. But the number of comprehensive combined test cases is large, and the test cost is high. Therefore, it is difficult for testers to simplify test cases while ensuring test results. This paper presented a technique on reducing test case set by using the representative characteristics of orthogonal test method. The proposed test technique is used in the distance calculation function test of train control mode for the LKJ basic control software. The actual application results show that the number of test cases is reduced by 77.5%, and the test effect can be guaranteed.